PERAN AKTOR KUNCI DALAM PEMILIHAN PENGHULU DI KAMPUNG SENGKEMANG KECAMATAN KOTO GASIB KABUPATEN SIAK TAHUN 2015 - Mar’atul Fadhlina; Ishak " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Village as a traditional government follow the system of democratic in the implementation of its government. Another form of democratic system in village is in the process of selecting urban village head. Urban village head is a bureaucrat who has the highest authority at the village level. Urban village head is very important in the process of running the village government towards the society welfare. The success of the selection of the urban village head not is separated from the role of key actors in winning their candidate. From this statement, it can be concluded that the research question of this research is to know how the role of key actors in selecting the urban village head.This research is a qualitative approach. This research was conducted in Sengkemang village. The technique used to collect data in this study were (1) interview, (2) Documentation; and (3) Study Library.The result of this research is the role of key actors in the selection of Sengkemang urban village head 2015 is very large. It can be seen from the success of key actors from candidate Adi Afri as the Selected urban village head in Sengkemang village. Adi Afri is a figure that is not very well known by the public, but the influence of key actor of Adi Afri, so that he can get a significant vote. The result of selecting urban vilage head in Sengkemang with significant vote is the success of key actors in playing their role. The numbers of DPT in Sengkemang village are 797 people and the numbers that use their voting are 652 votes.Keywords: role, Key Actor ,Selecting urban village head